2017
DOI: 10.1016/j.proci.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared laser-induced thermal grating spectroscopy in flames

Abstract: For the first time, laser-induced thermal grating spectroscopy (LITGS) in the spectral range around 3 μm is demonstrated as a versatile diagnostic tool. This spectral region is of particular interest in combustion diagnostics as many relevant species such as hydrocarbons and water exhibit fundamental vibrational modes and hence can be probed with high sensitivity. Another benefit of the IR-LITGS is that it allows performing spectroscopy in the infrared combined with signal detection in the visible. Hence, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In-depth theoretical discussions of LIGS grating formation [49][50][51][52] and its application for measurements in combustion relevant environments including flames [56][57][58][59], IC engines [44,60], flashboiling sprays [61], shock tubes [62], and rapid compression 01/14/2019 machines [63] are available in the literature. A brief description of the LIGS technique is provided here for the convenience of the reader.…”
Section: Laser Induced Grating Spectroscopy (Ligs)mentioning
confidence: 99%
“…In-depth theoretical discussions of LIGS grating formation [49][50][51][52] and its application for measurements in combustion relevant environments including flames [56][57][58][59], IC engines [44,60], flashboiling sprays [61], shock tubes [62], and rapid compression 01/14/2019 machines [63] are available in the literature. A brief description of the LIGS technique is provided here for the convenience of the reader.…”
Section: Laser Induced Grating Spectroscopy (Ligs)mentioning
confidence: 99%
“…[5]), Laser Induced Electrostrictive Gratings (LIEGS) (e.g. [6]), and Laser Induced Thermal Grating Spectroscopy (LITGS) [7][8][9][10][11][12][13][14][15][16][17][18][19]. The high pressures prevalent in gas turbines and rocket systems create significant challenges for optical diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…As detailed further on, this is because the signal intensity is proportional to the square of the induced refractive index fluctuation [15], which increases with the density of the mixture. A number of studies using LITGS have been used in nonreacting [8][9][10][11][12][13] and reacting [14][15][16][17][18][19] flows. Although LITGS can only be used in the presence of an absorbing species, LITGS also offers the advantage of significantly higher signal relative to LIEGS, and less stringent requirements on optical alignment relative to CARS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Sahlberg et al have demonstrated LITGS thermometry of flames using mid-IR pumps around 3000 nm and a cw probe laser at 457 nm to generate LITGS signals from combustion-generated H 2 O [28].…”
Section: Introductionmentioning
confidence: 99%